The bright side of high-heeled shoes - Fucks da Veiga, Paola Iana; Zanini Rosa, Priscila Bárbara; Horta Barbosa, Luiza; Pires Veiga Sanhudo, Marina; Motta Dias da Silva, Mariana; Moraes de Souza, Kerolene; Teixeira, Kellwin Nery; Sanhudo, Jose Antonio Veiga (Journal of the Foot & Ankle, 2025)
Objective: Wearing high heels is a common practice, especially among urban women, and is part of the social and professional environment for many people. Research on the subject often focuses on the harmful health effects of high heels, including discomfort and pain, musculoskeletal disorders, and foot deformities. Since few studies have assessed the subjective effects of high heels, the objective of this study was to investigate why people wear them or not. Methods: A cross-sectional, quantitative study was conducted using an online self-administered questionnaire that covered the participants’ profiles and reasons they wear or do not wear high heels. The convenience sample consisted of skeletally mature cisgender and transgender women aged ≥ 18 years. Data were collected between November 2023 and March 2024. Results: A total of 1100 responses were obtained, with a final sample of 801 participants. The variables significantly associated with wearing high heels were age, education, profession, approximate family income, and nutritional status. The reasons for wearing high heels included aesthetics ( 80%), feeling more beautiful (63%), better professional appearance (54%), and improved self-esteem (47%). Conclusion: Most participants wear high heels for aesthetic reasons, and more than half of those reported feeling more beautiful and feeling more professionally dressed. Although most participants who wear high heels experience pain (66%), there are still good subjective reasons to continue wearing them. Among those who reported not wearing high heels, the main reason was foot pain or discomfort. Level of evidence II; Cross-sectional, quantitative study.